Analysis of Technological Routes in the Plastics Supply Chain from Renewable and Non-renewable Sources in Brazil - Bianchini, Vivian Karina [UNESP] (2025)
Brazil has sought to develop polymers from renewable sources, known as biopolymers. This research aims to discuss that new forms of relationships exist in the plastic supply chain. In the quest for sustainable products, a new configuration of relationships has emerged between secondary plastic processing companies and the raw material source, now also originating from the sugarcane and alcohol sector, in addition to the traditional petrochemical sector. This new configuration brings about changes in the production strategies of these different plastic supply chains. A multicase study was conducted with semi-structured interviews, direct observation, and analysis of secondary data sources. The aim was to examine the practices adopted by companies, identifying relevant themes, both theoretically and practically, for the continued production of knowledge in a research line on production strategy and sustainable supply chain management.